Rainbow Washing in Human Resource Management: A Systematic Literature Review of Diversity Rhetoric and Authentic Inclusion - Sain, Zohaib Hassan; Rahimah, Anni (International Journal of Humanities, Education, and Social Sciences, 2025)
This study presents a systematic literature review (SLR) on the phenomenon of "rainbow washing"—the practice of promoting diversity rhetorically without enacting substantive change—within the context of Human Resource Management (HRM). While Diversity, Equity, and Inclusion (DEI) have become widely discussed in organizational discourse, there remains a lack of comprehensive analysis that critically examines the gap between symbolic commitments and authentic inclusion. This review addresses that gap by synthesizing existing research on how performative DEI efforts manifest, their operational mechanisms, and their impact on marginalized employees. A systematic search of Scopus and Web of Science databases was conducted in accordance with PRISMA guidelines, focusing on literature published between 2000 and 2024 using keywords such as “authentic inclusion,” “performative allyship,” “rainbow washing,” and “diversity rhetoric.” From an initial pool of 582 records, 25 studies met the inclusion criteria after a rigorous screening and quality appraisal process. The review identifies three critical patterns: (1) symbolic communication practices, including the use of simplified language and visual performativity; (2) the decoupling of HR systems, where recruitment, training, and accountability mechanisms serve reputational goals rather than internal transformation; and (3) the lived consequences for marginalized employees, such as heightened identity strain, workplace cynicism, and emergent forms of micro-resistance. Theoretically, this review contributes to the concept of Symbolic Inclusion by framing rainbow washing as a self-perpetuating organizational cycle. Practically, it provides HR professionals and policymakers with evaluative tools to distinguish between performative and impactful DEI initiatives. The study concludes that rainbow washing is a systemic organizational process with tangible psychosocial costs and calls for a paradigm shift from performative rhetoric to evidence-based, accountable inclusion practices. Future research should examine this phenomenon in non-Western contexts and explore the pivotal role of middle managers as agents of inclusive change.